An initial exploration of a community-based framework for educational equity with explicated exemplars. Issue 4 (4th July 2017) - Scheurich, James Joseph; Bonds, Vicki L.; Phelps-Moultrie, Jada A.; Currie, Brandon J.; Crayton, Troy A.; Elfreich, Alycia M.; Bhathena, Catherine D.; Kyser, Tiffany S.; Williams, Nathaniel A.
Abstract: Educational equity dominates discussions of US schooling. However, what 'educational equity' means is much contested in the scholarly literature and in public discourses. We follow the lead of scholars of color who have problematized the definition of educational equity. They have shown that the dominant, taken-for-granted definitions of equity which disguises the accumulation of societal and educational exclusions of and prejudices toward historically marginalized students, their families, and their communities. In response to this critique, we offer a new definitional framework for 'educational equity' that is community-based and, in our specific case, urban community-based. And, then, we will apply this new equity framework to three examples or 'exemplars' of education reform to explicate how they do and do not illustrate our framework. We will finish with a brief discussion, recommendations for future scholarship, and some concluding remarks.